Greening central bank policies: Euro area vs non-euro area EU member states - Uwe Vollmer (Intereconomics, 2024)
Climate change has become relevant for central banks worldwide, but they are adopting their instruments at different speeds. This article compares the reactions of the Eurosystem with those of the other EU central banks. Do these central banks differ in their efforts to make their own policies "greener"? The article argues that the options and constraints to react to climate change diverge between central banks.
Keywords: E58; E61; Q58; 330